Effectiveness of Social Forestry in Increasing Community Income in Mekakau Ilir District - Tibyan, Tibyan; Munajat, Munajat; Permata sari, Fifian (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
This research aims to analyze variables related to the effectiveness of social forestry in increasing people's income in Mekakau Ilir District. This research uses a type of quantitative research with descriptive statistics used to create a picture of the facts of the variables studied. Data collection techniques were carried out using observation, distributing questionnaires, and interviews. The analysis technique used is effectiveness analysis. The results of the research show that the level of effectiveness of social forestry in increasing the income of the Mekakau Ilir community is in the quite effective category, namely 49.78%. This was obtained by presenting the distribution of answers from 63 respondents.